Relevance of serum bile acid profile in the diagnosis of intrahepatic cholestasis of pregnancy in an high incidence area: Portugal - Brites, Dora (2017)
Objective(s): The present work was conducted to clarify the relevance of usual liver function tests, and define the most predictive serum bile acid profile for diagnosis of intrahepatic cholestasis of pregnancy (ICP). Study design: This study comprised 20 healthy nonpregnant women and 77 pregnant women in the last trimester of pregnancy, from which 38 were normal pregnancies, and 39 suffered from ICP. Liver function tests were evaluated by routine laboratory techniques, conjugated bile acids were analysed by high-performance liquid chromatography, and unconjugated forms were measured by an enzymatic–fluorimetric assay. Results: During the third trimester in normal pregnancy, increased concentration of conjugated species affected all primary bile acids, although only significantly for glycocholic acid. Moreover, deoxycholic acid proportion decreased when compared with healthy nonpregnant women. Important ICP-induced changes in serum profiles of amidated bile acids were observed, involving both a marked increase in cholic acid concentration and a shift towards a higher proportion of taurine-conjugated species. Among routine liver tests, alanine aminotransferase and conjugated bilirubin were the most common indicators of ICP. Conclusion(s): In the early diagnosis and follow-up of ICP, the most predictive and accurate markers (efficiency 100%) were: (i) TBA concentration in serum >11.0 μmol l−1: (ii) cholic/chenodeoxycholic acid ratio >1.5 and cholic acid percentage >42%: (iii) glycine/taurine bile acid ratio <1.0 or glycocholic acid concentration >2.0 μmol l−1. Accurate diagnosis based on sensitive biochemical markers followed by appropriate treatment may improve both pregnancy outcome and newborn prognosis.